(untitled) (Journal of Academic Research, 2025)
The study aimed to explore the role of green marketing in achieving a competitive advantage at Al-Ashab Company for Oils and Natural Products in Misrata. Data were collected using a structured questionnaire, and the research sample comprised 16 employees. The study adopted a descriptive-analytical methodology and revealed that Al-Ashab Company implements the concept of green marketing. The findings indicated a significant role of green marketing in enhancing the company’s competitive advantage. The study recommends that the company highlight its green branding on its products to strengthen customer trust, demonstrate its commitment to sustainable environmental practices, and foster a strong and positive corporate image in the market.